2020
DOI: 10.1111/petr.13793
|View full text |Cite
|
Sign up to set email alerts
|

The incidence, risk factors, and outcomes of acute graft‐vs‐host disease in pediatric T‐cell‐replete haploidentical hematopoietic stem cell transplantation

Abstract: The specific description, risk factors, and outcomes of aGVHD in pediatric haplo-HSCT using TCR protocols without PT-Cy have not been well described previously. We evaluated the incidence, risk factors, and outcomes of aGVHD in 350 consecutive pediatric patients receiving TCR haplo-HSCT without PT-Cy according to the Glucksberg and NIH aGVHD classifications between January 2015 and December 2017 at Peking University Institute of Hematology. The cumulative incidences of How to cite this article: Tang F-F, Cheng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…TRM in infants and young patients in this study was not higher than that reported in previous studies conducted at our institute 27,28 . We found that the cumulative incidence rates of aGVHD and cGVHD in this study were parallel to the incidence in children of all age groups of historical controls in our center 29,30 . Tang et al.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…TRM in infants and young patients in this study was not higher than that reported in previous studies conducted at our institute 27,28 . We found that the cumulative incidence rates of aGVHD and cGVHD in this study were parallel to the incidence in children of all age groups of historical controls in our center 29,30 . Tang et al.…”
Section: Discussionsupporting
confidence: 49%
“…27,28 We found that the cumulative incidence rates of aGVHD and cGVHD in this study were parallel to the incidence in children of all age groups of historical controls in our center. 29,30 Tang et al reported that the 3-year cumulative incidence of relapse was significantly lower in patients with cGVHD than in those without cGVHD (17.6% vs. 27.2%; p = .009), 30 31 Therefore, we speculate that the improved prognosis observed in this study may be related to the relatively high rate of cGVHD and its consequent relatively low relapse rate. The PTCy-based approach can be applied to either reduced-intensity or myeloablative regimens and has a low incidence of both acute and chronic GVHD.…”
Section: Discussionsupporting
confidence: 44%